Community recording and monitoring of vulnerable sites in England - Wragg, E; Cohen, N; Milne, G; Ostrich, S; Nimura, C (Oxbow Books, 2017)
Significant archaeological sites along England’s sinuous coast and on the foreshores of tidal estuaries are continually eroded by winds, waves and tidal scour. Alarmed by the rate of loss, the location of many of these sites has been noted during the national ‘Rapid Coastal Zone Assessment Survey’ programme initiated by English Heritage (now Historic England) and also by archaeological groups around the country. But until recently there had been no national standardised system in place to record these vulnerable sites in detail or to regularly monitor their fate over the longer term. CITiZAN: the Coastal and InterTidal Zone Archaeological Network provides a systematic national response to natural and anthropogenic forces threatening coastal and intertidal archaeology in England. The project employs similar methodologies to the recording and monitoring of fragile intertidal archaeology as its sister project, the Thames Discovery Programme, which has for the last decade monitored the archaeology of the Greater London Thames foreshore. Both projects employ a system of community-based training and outreach programmes, creating an infrastructure to support a network of volunteers with the skills and systems in place to enable them to monitor and survey the highly significant but threatened archaeological sites around England’s coast and foreshores. This paper looks at the evolution of the methodologies employed by these projects, both archaeological and educational, as well as the implementation of standardised recording and monitoring using crowd-sourced data, and presents key findings from this ‘citizen science’ programme. Coastal erosion can rarely be halted, but the hope of TDP and CITiZAN is to involve the public in such a way that will help ensure archaeological sites can be recorded before they are destroyed.